Pizza cats - Herman, Gail, 1959-; Del Carmen, Louie; Peters, James (James Edwards) (New York : Simon Spotlight/Nickelodeon, 1999)
After making a huge mess in the storeroom, Tommy, Chuckie, Phil, and Lil persuade Pete to let three stray cats live in his pizza parlor.
Keywords: Pizza -- Fiction; Cats -- Fiction; Toddlers -- Fiction